MODEL PERILAKU PENGGUNA APLIKASI QRIS DAN HUBUNGANNYA TERHADAP IMPULSIVE BUYING - Akhwanul Akhmal; Metya Lutviani (JURNAL LENTERA BISNIS, 2024)
This type of research is quantitative research that assesses the QRIS user behavior model and its relationship with Impulsive Buying. Research was conducted on people who use QRIS in carrying out online and offline transactions. This research uses the UTAUT approach. This research also supports IKU 1 Polytechnic LP3I Jakarta, namely the work readiness of graduates because of. In this study there are 4 independent variables (X) and 2 dependent variables (Y), namely, performance expectancy (X1), effort expectancy (X2), social influence (X3), facilitating conditions (X4), behavioral intention (Y1), Impulsive Buying (Y2) Respondents in this study were LP3I Jakarta polytechnic students who belonged to generation Z with a birth year range of 2002-2006 who used QRIS as many as 100 people. For more accurate results, respondents taken were those who had used QRIS >5x. The results of hypothesis testing in this research prove that performance expectancy has a significant positive effect on user behavior intention. This means that performance expectancy influences behavioral intention that the use of QRIS digital payments is very fast and efficient. Hypothesis testing in this research proves that effort expectancy has a significant positive effect on user behavior intention. This means that effort expectancy influences behavior intention so that those using QRIS digital payments can learn and become more skilled in using the new information system